Does isolation of the left atrial posterior wall improve clinical outcomes after radiofrequency catheter ablation for persistent atrial fibrillation?: A prospective randomized clinical trial. (15th February 2015) - Kim, Jin-Seok; Shin, Seung Yong; Na, Jin Oh; Choi, Cheol Ung; Kim, Seong Hwan; Kim, Jin Won; Kim, Eung Ju; Rha, Seung-Woon; Park, Chang Gyu; Seo, Hong Seog; Oh, Dong Joo; Hwang, Chun; et al.
Abstract: Introduction: Although posterior wall of left atrium (LA) is known to be arrhythmogenic focus, little is known about the effect of posterior wall isolation (PWI) in patients who undergo radiofrequency catheter ablation (RFCA) for persistent atrial fibrillation (PeAF). Methods: We randomly assigned 120 consecutive PeAF patients to additional PWI [PWI (+), n = 60] or control [PWI (−), n = 60] groups. In all patients, linear ablation was performed after circumferential pulmonary vein isolation (PVI). Linear lesions included roof, anterior perimitral, and cavotricuspid isthmus lines with conduction block. In PWI (+) group, posterior inferior linear lesion was also conducted. Creatine kinase-MB (CK-MB) and troponin-T levels were measured 1 day after RFCA. LA emptying fraction (LAEF) was assessed before and 12 months after RFCA. Results: A total of 120 subjects were followed for 12 months after RFCA. There were no significant differences between two groups in baseline demographics and LA volume (LAV). The levels of CK-MB and troponin-T and procedure time were not significantly different between the groups. AF termination during RFCA was more frequently observed in PWI (+) than control ( P  = 0.035). During follow-up period, recurrence occurred in 10 (16.7%) patients in PWI (+) and 22 (36.7%) in control ( P  = 0.02). The change in LAEF was not significantly different between the groups. On multivariate analysis, smaller LAV and additional PWI were independently associated with procedure outcome. Conclusions: PWI in addition to PVI plus linear lesions was an efficient strategy without deterioration of LA pump function in patients who underwent RFCA for PeAF.